2015
DOI: 10.1186/s13578-015-0035-9
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous hydrogen sulfide restores cardioprotection of ischemic post-conditioning via inhibition of mPTP opening in the aging cardiomyocytes

Abstract: The physiological and pathological roles of hydrogen sulfide (H2S) in the regulation of cardiovascular functions have been recognized. H2S protects against the hypoxia/reoxygenation (H/R)-induced injury and apoptosis of cardiomyocytes, and ischemic post-conditioning (PC) plays an important role in cardioprotection from H/R injury in neonatal cardiomyocytes but not in aging cardiomyocytes. Whether H2S is involved in the recovery of PC-induced cardioprotection in aging cardiomyocytes is unclear. In the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 44 publications
6
57
0
Order By: Relevance
“…This endogenous protective-adaptive intervention suppresses spontaneous Ca 2+ oscillations and inhibits mPTP opening [22], contributing to the maintenance of mitochondrial homeostasis, attenuation of oxidative stress, and alleviation of apoptosis [23]. IPO-induced protection against IR injury has been confirmed in multiple organs [11,19,22]. Consistent with these studies, we found that IPO markedly attenuated IIR injury as characterized by reduced histological damage and lower levels of serum biomarkers.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This endogenous protective-adaptive intervention suppresses spontaneous Ca 2+ oscillations and inhibits mPTP opening [22], contributing to the maintenance of mitochondrial homeostasis, attenuation of oxidative stress, and alleviation of apoptosis [23]. IPO-induced protection against IR injury has been confirmed in multiple organs [11,19,22]. Consistent with these studies, we found that IPO markedly attenuated IIR injury as characterized by reduced histological damage and lower levels of serum biomarkers.…”
Section: Discussionsupporting
confidence: 86%
“…IPO is defined as rapid intermittent interruptions of blood flow in the early phase of reperfusion that mechanically alter the hydrodynamics of reperfusion. This endogenous protective-adaptive intervention suppresses spontaneous Ca 2+ oscillations and inhibits mPTP opening [22], contributing to the maintenance of mitochondrial homeostasis, attenuation of oxidative stress, and alleviation of apoptosis [23]. IPO-induced protection against IR injury has been confirmed in multiple organs [11,19,22].…”
Section: Discussionmentioning
confidence: 97%
“…Because aging in general decreases antiapoptotic pathways and increases pro‐apoptotic pathways, other mitochondrial proteins that are known to inhibit mPTP are probably also reduced by aging; these may include HSP75 (Wang et al ., ), HSP60 and HSP90 (TRAP1; Altieri, ), which are induced by the UPR(mt), and antiapoptotic proteins, such as BCL‐2 and BCL‐x L (Jonas et al ., ). Moreover, an increasing number of metabolites were reported to control the mPTP directly or indirectly, for example, mitochondrial cAMP and cyclic nucleotide phosphodiesterase (CNP; Baburina et al ., ), polyphosphate (Baev et al ., ), spermine (Wei et al ., ), and H 2 S (Li et al ., ). These effects are probably also modulated by aging.…”
Section: The Enhancement Of Mptp Opening By Aging Is Mediated By Aginmentioning
confidence: 97%
“…A recent study on lifespan extension in C. elegans by germline loss shows that lifespan extension in this case depends on two independent pathways, one of which is mROS dependent (UPRmt) and the other not (the H 2 S pathway; Wei & Kenyon, ). However, H 2 S, similar to UPRmt, also inhibits the mPTP (Li et al ., ). In a study of a very large number of C. elegans lifespan modulations by mutations and environmental manipulations, it was shown that lifespan correlates negatively with the frequency of ‘mitoflashes’ at an early adult age (Shen et al ., ).…”
Section: Lifespan Extension By Mutations and Caloric Restriction Mostmentioning
confidence: 97%
“…Several studies have indicated that the mitochondriadependent apoptosis signaling pathway is more active in multiple organs of the elderly, for instance, muscle [18], heart [19]. Our previous study showed that the increased expression of Omi (also known as HtrA2) enhances MI/R injury in aged hearts [9] by inducing myocardial mitochondrial apoptosis [11].…”
Section: Discussionmentioning
confidence: 99%